Analysis Of Contact Disconnection In A Low Voltage Circuit Breaker - Mačák, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This work deals with a simulation of plasma phenomenon and with a simulation of an arc ingnition between contacts in a low voltage circuit breaker. Simulations were made in Ansys Fluent with the usage of MHD (Magnetohydrodynamic) add-on module and additional UDFs (User Defined Functions). Mathematical model presented in this work connects electric and magnetic field, which is not possible in Ansys Fluent by default.
Keywords: Plasma; Electric arc; Ansys Fluent; Circuit breaker; MHD